Absorption spectra peculiarities of thin films of (CsCu₂Cl₃)₁₋ₓ(CsCu₂l₃)ₓ system. - Yunakova, O.N.; Miloslavsky, V.K.; Kovalenko, E.N. (Functional Materials, 2004)
Absorption spectrum of (CsCu₂Cl₃)₁₋ₓ(CsCu₂l₃)x thin films has been investigated in the fundamental band region. The CsCu₂Cl₃ solid solutions have been found to be formed within the concentration ranges 0<x<0.08 and 0.34<x<1. In the 0.1<x<0.6 range, there is a mixture of two phases in the thin films, namely, of CsCu₂Cl₃-₃xI₃x solid solutions and CsCu₂Cl₃:Cu⁺. The latter phase appears as a result of a strong disordering of the CsCu₂Cl₃ anionic sublattice as Cl⁻ ions are substituted by l- ones having a larger radius. A new absorption band corresponds to that phase in the absorption spectrum peaked at 4.8 eV; it is associated with the excitation of quasi-impurity Cu⁺ ions in the cationic sublattice of the compound in the vicinity of l- ions. The concentration dependences of the exciton band position Eex(x) and half-width GA A A MA(x) are typical of solid solutions and confirm the formation thereof in the mentioned concentration ranges.